Unraveling the effects on lithium-ion cathode performance by cation doping M–Li2CuO2 solid solution samples (M = Mn, Fe and Ni). Issue 14 (20th March 2020) - Martínez-Cruz, M. A.; Yañez-Aulestia, A.; Ramos-Sánchez, G.; Oliver-Tolentino, M.; Vera, M.; Pfeiffer, H.; Ramírez-Rosales, D.; González, I.
Abstract : Manganese partial substitution reveals a drastic improvement in the electrochemical stability of Li2 CuO2 during the charge/discharge processes, this is attributed to the increase in the superexchange interaction between copper sites and manganese. Abstract : Cation doping is one of the most dynamic strategies to enhance the electrochemical properties of cathode materials for lithium-ion batteries. Nevertheless, the maximum partial substitution capacity depends on the solubility of each metal ion, and so the formation of impurities is a very common consequence. Thus, the correlation between electrochemical performance and the doping effect is frequently unknown. In this study, the effect of the partial substitution of copper by manganese, iron or nickel in Li2 CuO2 is evaluated, as well as the effect on the electrochemical performance of the modified Li2 CuO2 samples as lithium ion battery cathode materials. XRD characterization confirmed single phase formation for all samples, and the incorporation of the transition metal in the Li2 CuO2 structure was evaluated by XRD profile fitting, EPR and 7 Li-NMR. The results showed modifications in intra- and inter-chain interactions, associated with the variations in the Cu–O–Cu bond angle and changes in magnetic order, due to the presence of the doping transition metal. Among all samples, only manganese partial substitution reveals a drastic improvement in the electrochemical stability during the charge/discharge processes even at potentials higher than 3.9 V. It was corroborated that the higher stability is attributed to (i) the increase in the superexchange interactions between the copper sites and manganese, directly modifying lithium diffusivity and electronic conductivity, both inferred from dynamic thermogravimetric analysis for CO2 sorption and conductivity tests, respectively and (ii) the lower propensity to enable O2 evolution during several charge cycles. These results are totally attributed to manganese cation partial substitution, which has a huge impact on the utilization of copper-based materials in real applications.